QUANTIFICATION OF ECONOMIC AND SOCIAL RISKS OF DEBRIS FLOWS FOR THE BLACK SEA COASTAL REGION OF THE NORTH CAUCASUS - Vyacheslav L. Baburin; Sofia A. Gavrilova; Peter Koltermann; Yury G. Seliverstov; Sergey A. Sokratov; Aleksandr L. Shnyparkov (Geography, Environment, Sustainability)
Debris flows are the most frequent and disastrous natural hazards among other exogenic processes at the Black Sea coastal region of the North Caucasus. Numerous debris flow releases are reported every year between Novorossiysk and Krasnaya Polyana. The debris flows bring economic losses, and sometimes loss of human lives. Quantification of the economic, individual and collective debris flows risk is based on their spatial distribution, repeatability, debris flows’ regime, as well as economical and social characteristics of the territory accounted for. Estimation of the individual debris flow risk shows that the level of such risk corresponds to “allowable” and “acceptable” degrees [Vorob’ev, 2005] - less than 3,3 × 10-6. The maximal values of the economic debris flow risk are estimated in the Adler region - more than 1 mln. rub. per year.